2018
DOI: 10.1016/j.nicl.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal language-related oscillatory responses in primary progressive aphasia

Abstract: Patients with Primary Progressive Aphasia (PPA) may react to linguistic stimuli differently than healthy controls, reflecting degeneration of language networks and engagement of compensatory mechanisms. We used magnetoencephalography (MEG) to evaluate oscillatory neural responses in sentence comprehension, in patients with PPA and age-matched controls. Participants viewed sentences containing semantically and syntactically anomalous words that evoke distinct oscillatory responses. For age-matched controls, sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…One result which does not easily fit under the prediction account is the gamma power increase in sentences with incongruent endings compared to congruent ones, reported in Wang et al (2018a). Mixed gamma findings like this one, or the absence of gamma effects in Kielar et al (2015Kielar et al ( , 2018 and Wang, Jensen, et al (2012) for example, might be at least partially accounted for by the fact that finding and/or interpreting effects of cognitive manipulations on gamma power can be challenging. This is because there are multiple potential pitfalls that have to be taken into account in the analysis procedures.…”
Section: Semantic Anomaliesmentioning
confidence: 93%
See 2 more Smart Citations
“…One result which does not easily fit under the prediction account is the gamma power increase in sentences with incongruent endings compared to congruent ones, reported in Wang et al (2018a). Mixed gamma findings like this one, or the absence of gamma effects in Kielar et al (2015Kielar et al ( , 2018 and Wang, Jensen, et al (2012) for example, might be at least partially accounted for by the fact that finding and/or interpreting effects of cognitive manipulations on gamma power can be challenging. This is because there are multiple potential pitfalls that have to be taken into account in the analysis procedures.…”
Section: Semantic Anomaliesmentioning
confidence: 93%
“…In a series of studies which examined the link between neural oscillations and semantic processing, Kielar et al (2014Kielar et al ( , 2015Kielar et al ( , 2018 have consistently found an alpha/beta power decrease in response to semantic anomalies in a sentence, and in two out of three studies (Kielar et al, 2014(Kielar et al, , 2015, they also reported a delta/theta power increase in response to semantic anomalies. One reason Kielar et al (2018) may not have observed an increase in theta could be their relatively small sample size: 15 compared to 28 and 20 participants in their other studies. Five further studies (Bastiaansen & Hagoort, 2015;Davidson & Indefrey, 2007;Hagoort et al, 2004;Hald, Bastiaansen, & Hagoort, 2006;Wang, Zhu, & Bastiaansen, 2012) also reported a theta increase in response to semantic anomalies.…”
Section: Semantic Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially relevant when the effects might occur later with respect to stimuli onset, as in the current setting, where differences between controls and patients in early, low-level visual processes are not expected, while divergence in later stages is predicted by both behavioral evidence and neuroanatomical findings. Furthermore, increased latency in response to linguistic stimuli have been observed in svPPA patients, and analyses of oscillatory behavior might be more sensitive than ERPs in detecting abnormalities in slow neural responses with increased trial-by-trial variability and thus decreased phase-locking (Kielar et al, 2018). Second, we aimed at providing functional interpretation of our findings.…”
Section: Meg Protocol and Analysesmentioning
confidence: 98%
“…MEG has only been deployed recently to investigate PPA (e.g., Kielar et al, 2018), but has already shown its potential as a tool to study the neurophysiological signatures of network-level alterations due to neurodegenerative disorders. It can be instrumental in identifying syndromespecific changes in the spectral properties of oscillatory responses (Ranasinghe et al, 2017;Sami et al, 2018).…”
Section: The Latency Of the Dorsal Activation Indicates Slow Serial mentioning
confidence: 99%